Vibration Analysis of Different Types of Porous FG Circular Sandwich Plates - Mohsen Rahmani; Younes Mohammadi; Farshad Kakavand (International Journal of Advanced Design and Manufacturing Technology, 2019)
For the first time, by applying a modified high order sandwich plates theory, vibration behaviour of two types of porous FG circular sandwich plates are investigated. In the first type, the face sheets and in the second one, the core is made of FGM which is modelled by power law rule that is modified by considering two types of porosity distributions. All materials are temperature dependent and uniform temperature distribution is used to model the effect of the temperature changing in the sandwiches. Governing equations are obtained by the Hamilton's energy principle and solved by Galerkin method for a clamped boundary condition. To verify the results, they are compared with FEM results obtained by Abaqus software and for special cases with the results in literatures.